1643. A scoping review of pediatric latent tuberculosis care cascades: Initial steps are lacking. (31st December 2020) - Campbell, Jeffrey; Sandora, Thomas; Haberer, Jessica
Abstract: Background: Each year an estimated 1 million children develop and ~200, 000 die from tuberculosis (TB). The WHO has named identification and treatment of latent tuberculosis infection (LTBI) one of the cornerstones of efforts to eliminate TB by 2030. Identification and treatment of pediatric LTBI requires completion of a complex care cascade. While attention has been given to LTBI care cascades in adults, to date there has been no attempt to map literature on the pediatric LTBI care cascade. Facilitators and barriers to retention in steps of the pediatric LTBI care cascade Methods: We systematically searched PubMed, CINAHL, Cochrane and Embase databases for papers and abstracts describing screening, diagnosis, and treatment of pediatric LTBI. We categorized literature using seven step-offs in the pediatric LTBI care cascade, extrapolated from prior studies focused on adults: 1) intention to screen to initial test, 2) initial test to receipt of results, 3) receipt to referral for evaluation, 4) referral to completion of evaluation, 5) completion to treatment recommendation, 6) recommendation to treatment acceptance/initiation, and 7) initiation to treatment completion. Our aim was to assess factors that facilitated and inhibited completion of each cascade step, and to identify knowledge gaps in this literature. Results: We identified 137 studies that met inclusion criteria. Most studies described multiple step-offs in the care cascade, although the focus of most (120/137 studies) was on initiation and completion of LTBI therapy (the final step in the care cascade). Several effective strategies to improve medication adherence were described, including selective use of nursing visits, directly observed therapy, shorter treatment regimens, and peer counseling. Reports of facilitators and barriers for retention in upstream step-offs in the cascade were scarce, revealing a lack of published evidence for how to retain children from pre-screening to treatment initiation (Table). Conclusion: While existing literature describes LTBI treatment initiation and completion in children, our analysis reveals a lack of data guiding retention of children from LTBI screening through treatment initiation. This review highlights the need to further understand early steps of the care cascade, in order to help alleviate the burden of TB in children. Disclosures: Jessica Haberer, MD, MS, Merck (Consultant)